A general solution for leakage through geomembrane defects overlain by saturated tailings and underlain by highly permeable subgrade - Rowe, R. Kerry; Fan, Jiying (Geotextiles and geomembranes, 2022)
Experimental data is presented for leakage through slits, square, and rectangular geomembrane defects overlain by silty sand tailings and underlain by a well-graded gravel. The rectangular GMB defects have a range of widths, B, lengths, L, and aspect ratios (L/B), and ratios of defect length to thickness of tailings above the geomembrane (L/T). A blade cut slit (or simulated stress crack) widens to an extent dependant on the subgrade and stress level. For L= 100 mm, increasing B (0.15 < B/L ≤ 1) from 1.6 (slit) to 100 mm (square), decreases the leakage from about twice to essentially the same as that for a circular hole of equal area. The ratio (h1/H) of head loss within the hole, h1, relative to the total head loss, H, is independent of loading conditions and constant for any particular hole shape (B/L), area (B∙L), and relative depth (L/T). A semi-empirical general solution is developed for a rectangle within the range of 0 ≤ B/L ≤ 1 with the solution converging to that for a strip for B/L→ 0 and to a circle for B/L→ 1. The solution gives calculated leakage in encouraging agreement with the experimental data. •Investigates the factors affecting leakage through a rectangular hole in a geomembrane overlain by tailings.•Studies how hole geometry affects leakage.•Provides a semi-empirical general solution for predicting leakage through quasi circular, rectangular, and strip (L » B) holes.•Investigates the physical and hydraulic response of a blade cut slit with flat and uneven ground conditions.